Clinician and staff perspectives on potential disparities introduced by the rapid implementation of telehealth services during COVID-19: a mixed-methods analysis. Issue 7 (16th June 2021) - Phimphasone-Brady, P; Chiao, J; Karamsetti, L; Sieja, A; Johnson, R; Macke, L; Lum, H; Lee, R; Farro, S; Loeb, D; Schifeling, C; Huebschmann, A G
Abstract: The COVID-19 pandemic has rapidly altered ambulatory health care delivery and may have worsened disparities in health care access. To assess the telehealth implementation experiences of ambulatory personnel in different disciplines and their perspectives on potential telehealth disparities, and to make recommendations for more equitable telehealth delivery. We used a convergent parallel mixed-methods design. Clinic managers from geriatric medicine, internal medicine, and psychiatry e-mailed a survey to clinicians and staff regarding experiences with telehealth care delivery. Quantitative survey responses were analyzed with Fisher's Exact tests. Qualitative responses were coded thematically. Recommendations were categorized by type of implementation strategy. Quantitative and qualitative findings on telehealth disparities were merged in a joint data display. Respondents ( n = 147, 57% response rate) were distributed across three specialties: 66% internal medicine, 19% psychiatry, and 14% geriatric medicine. Prior to 2020, 77% of clinicians had never delivered telehealth services. By Spring 2020, 78% reported conducting more than half of clinic visits by telehealth. Among clinicians, 52% agreed/strongly agreed that rapid telehealth implementation exacerbated access to care disparities to: older adult patients, those with limited internet access, and those needing interpretation services. Staff expressed similar difficulties with telehealth set-up especially for these patients. To improve telehealth equity, clinicians recommended to: (i) change infrastructure; (ii) train and educate stakeholders; and (iii) support clinicians. Clinicians and staff reported specific subpopulations had challenges in accessing telehealth visits. To avoid perpetuating telehealth access disparities, further co-discovery of equitable implementation strategies with patients and clinics are urgently needed. Abstract : Primary care and mental health clinicians and staff identified a 舖digital divide舗 that challenged remote clinical care during the early COVID-19 pandemic due to limited access to high-speed internet service and/or limited digital literacy. Actionable recommendations, resources and tools were provided to minimize this divide.